AN ASSESSMENT OF ADOPTION OF IMPROVED PRODUCTION PRACTICES AMONG WATERMELON FARMERS IN JIGAWA STATE, NIGERIA - Inuwa, Abdullahi M.; Muhammad, Musa B.; Abdulsalam, Rakiya Y. (FUDMA JOURNAL OF SCIENCES, 2025)
This study examines the factors influencing the adoption of improved watermelon production practices among farmers in Jigawa State, Nigeria, with a focus on enhancing agricultural productivity and sustainability. Watermelon is an important cash crop in Jigawa State, contributing significantly to farmers' income and rural development. Despite the introduction of improved watermelon production practices to watermelon farmers, the adoption rates of such practices remain low. This study focuses on analysing the socio-economic characteristics of watermelon farmers, their level of awareness, adoption rate and factors influencing the adoption of improved watermelon production practices. Using a multi-stage sampling technique, data were collected from 236 watermelon farmers across three Local Government Areas (LGAs) in the state. Descriptive statistics and a Tobit regression model were employed to analyse the data. The findings revealed that most farmers are within their productive age range, with moderate household sizes and farm sizes averaging 1.75 hectares. Majority (94.1%) of respondents are aware of improved seed varieties, adoption rates for practices like storage techniques remain low at 35.0 percent. Farm size and Extension contacts were significant positive predictors of adoption, while larger household sizes and farming experience negatively influenced adoption. The study recommends strengthening institutional support and addressing socio-economic constraints to bridge the gap between awareness and full adoption of improved production practices. These findings provide valuable insights for policymakers, agricultural extension officers, and development organisations aiming to boost sustainable production of watermelon, contributing to food security and rural development in the state.
Keywords: Adoption; Watermelon; Improved Production Practices; Jigawa State